Carbon Footprint Assessment of Internal Transportation of Laed Factory and Guideline to Reduce Carbon Footprint - Chaiyaboot, Theema; Kosanlavit, Waraporn; Kongritti, Nirun; Noinumsai, Napat (Asia Pacific Journal of Religions and Cultures, 2021)
Greenhouse Gas emission is a cause of global warming problem. Carbon footprint from the manufacture of a product indicates the amount of greenhouse gas emitted from the manufacture of that product. This research work has two objectives, namely, 1) to assess the carbon footprint of internal transportation of lead factory, and 2) to find ways to reduce carbon footprint and greenhouse gas that is emitted from internal transportation of lead factory that recycles used batteries in order to get lead that is the raw material for the manufacture of lead ingot, the total weight of with is 1,000 kilograms. The findings from the study show that the carbon footprint of the internal transportation of raw material in the preparation of the raw material is higher than the carbon footprint from other transportation process. It is found out that the carbon footprints are 143.23, 112.33, 78.46 kg CO2e per product ton for 2018, 2019 and 2020, respectively. It is also found out that the carbon footprints of the internal transportation in the factory for the production of lead ingot are lowest, or 0.22, 0.97, 0.90 kg CO2e per product ton in 2018, 2019 and 2020, respectively. As for the transportation for the preparation of raw material for producing pure lead and supportive process, it is discovered that the carbon footprints from the production of rough lead are the highest ones in all the three years, followed by the carbon footprint from the preparation of raw material for lead with calcium. Concerning the carbon footprints from the transportation of raw materials, sorted by products, it is found out that the carbon footprint from the transportation of raw material for the production of pure lead is the highest of all.